Looking for Work in Post-Socialist China : Governance, Active Job Seekers and the New Chinese Labour Market. - Xu, Feng (Routledge contemporary China series., 2012)
Unemployment is one of the most politically explosive issues in China and has gained further prominence as a result of the present global financial crisis. The novelty, urgency, and complexity of Chinese unemployment have compelled the government to experiment with policy initiatives that originate in the West. This book argues that although China is not a liberal democracy, it has turned to neo-liberal forms of governance to deal with unemployment, which now function alongside pre-existing Chinese modes of governance. This book examines the initiatives which represent China's attempt to institutionalize and humanize its approach to governance: these initiatives include training programmes; counselling; a web-based national labour-market information network; insurance; and using community (shequ) organizations as the base for new mechanisms of governance and informal job generation. Based on extensive original research including semi-structured interviews, the book discusses the ways in which the government combines the new techniques with old campaign-style policy techniques. The author argues that these multiple modes of governance make the state's power visible in the new Chinese labour market, and at the same time run the risk of policy incoherence or even failure.